Mechanisms of Developing Students Professional Competence in Engineering Activities - Avazov Jo'rabek Donievich (Genius Publishing Group, 2022)
The article describes the mechanisms of development of professional competence of students in engineering activities in higher education institutions on the example of the development and use of data maps in the form of a systematic list of textual and graphical data on specific topics of "Engineering and Computer Graphics".
Keywords: Higher; Educational; International; Student